2021
DOI: 10.1007/s10479-021-04459-5
|View full text |Cite|
|
Sign up to set email alerts
|

Joint optimisation of drone routing and battery wear for sustainable supply chain development: a mixed-integer programming model based on blockchain-enabled fleet sharing

Abstract: Alongside the rise of ‘last-mile’ delivery in contemporary urban logistics, drones have demonstrate commercial potential, given their outstanding triple-bottom-line performance. However, as a lithium-ion battery-powered device, drones’ social and environmental merits can be overturned by battery recycling and disposal. To maintain economic performance, yet minimise environmental negatives, fleet sharing is widely applied in the transportation field, with the aim of creating synergies within industry and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…Several theoretical studies have shown the advantages of a truck-drone delivery system. Fleet sharing is commonly used in the transportation sector to maintain economic performance while minimizing environmental impacts (Xia et al, 2021 ).…”
Section: Cooperation Of Drones With Trucks To Deliver Postal Packagesmentioning
confidence: 99%
“…Several theoretical studies have shown the advantages of a truck-drone delivery system. Fleet sharing is commonly used in the transportation sector to maintain economic performance while minimizing environmental impacts (Xia et al, 2021 ).…”
Section: Cooperation Of Drones With Trucks To Deliver Postal Packagesmentioning
confidence: 99%
“…It also explores phenomena such as resilience, sustainability, green, circular SC as the future application areas. The potential SC application areas for BT discussed in the literature are Food SC (Behnke & Janssen, 2020 ; Bumblauskas et al, 2020 ; Kittipanya-ngam & Tan, 2020 ; Liu et al, 2020 ; Vivaldini, 2021a ), Agricultural SC (Hu et al, 2021 ; Liu et al, 2020 ; Mishra & Maheshwari, 2021 ; Mukherjee et al, 2021 ), SC Risk Management (Choi et al, 2019 ; Manupati et al, 2022 ; Rauniyar et al, 2022 ; Shashi et al, 2020 ), Sustainable SC (Gong et al, 2022b ; Khan et al, 2022b ; Liu et al, 2021c ; Wang et al, 2022 ; Xia et al, 2021 ), etc. 65 studies fall under this heading as listen in Table 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Constraints (24) and ( 25) specify the total number of independent blocks produced in the second layer. Constraints (26) and (27) show non-negative continuous and binary decision variables, respectively.…”
Section: Problem Descriptions and Modelsmentioning
confidence: 99%
“…The results showed that the overall profits of the supply chain grow with the blockchain adoption due to the two reasons of sharing information and reducing the cost of transactions. Xia et al 26 implemented fleet sharing through blockchain technology in the last mile delivery problem. Their results revealed that the higher the sharing power, the lower the costs.…”
mentioning
confidence: 99%